Systematic Analysis of the Current Academic Research on Social Media Marketing - Klepek Martin (Scientific Annals of Economics and Business, 2017)
With the advent of social media where customers have the technical ability to upload own content the change occurred in some of the communication habits online. This world of constant communication is a challenge for businesses as well researchers. Academic research in this area is bringing valuable insights into people attitudes and behaviour on the social media. What is the current situation and where the research field is heading is a question of high importance. This study uses the systematic approach to reviewing the literature and to show the development of publications produced at Czech universities. Although the results show an increasing number of studies, Czech research is lagging behind other similar countries. Compared with the best countries, it is lagging behind in the number of quotations per article. On the basis of these analyses, suggestions for future research that can help to promote future theory development are proposed.